2009
DOI: 10.2172/989057
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Telemetry Evaluation of Juvenile Salmonid Passage and Survival at John Day Dam with Emphasis on the Prototype Surface Flow Outlet, 2008

Abstract: Executive SummaryImproving survival rates of juvenile salmonids through the Federal Columbia River Power System (FCRPS) continues to be a high priority for the U.S. Army Corps of Engineers, Portland District. Many of these fish are from populations listed as threatened or endangered under the Endangered Species Act of 1973. Increased survival rates are necessary to meet performance standards set forth in the 2008 Biological Opinion (BiOp) on FCRPS operations. The BiOp mandates 96% and 93% survival rates be ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

6
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…This study, however, was affected by very high spill through adjacent bays during a year of above-average river discharge. Weiland et al 2009 Engineering and model studies examining skeleton bays as potential SFO sites were conducted in the 1990s (Montgomery Watson et al 2000). At a physical model at the USACE Engineering, Research, and Development Center, observations of a 20,000-cfs SFO in a skeleton bay showed strong forebay flow nets, indicating a potential for fish to discover the SFO flow.…”
Section: Surface-flow Outlet Developmentmentioning
confidence: 99%
“…This study, however, was affected by very high spill through adjacent bays during a year of above-average river discharge. Weiland et al 2009 Engineering and model studies examining skeleton bays as potential SFO sites were conducted in the 1990s (Montgomery Watson et al 2000). At a physical model at the USACE Engineering, Research, and Development Center, observations of a 20,000-cfs SFO in a skeleton bay showed strong forebay flow nets, indicating a potential for fish to discover the SFO flow.…”
Section: Surface-flow Outlet Developmentmentioning
confidence: 99%
“…Virtual releases were defined by detections on the forebay entrance array or spillway array to identify groups of fish for estimating dam-passage and spillway-passage survival rates, respectively. Weiland et al (2009) …”
Section: Transport and Releasementioning
confidence: 99%
“…In the Columbia River, scientists have identified acoustic telemetry as being an essential technology for observing the behavior and estimating the survival of juvenile salmonids passing through the side channels and the main stem FCRPS (Faber et al 2001;McComas et al 2005;Ploskey et al 2007;Ploskey et al 2008;Clemens et al 2009). Hydroelectric dams provide various routes of passage where mortality becomes pathway-specific depending on the physical properties of the technical installation (Coutant and Whitney 2000;Muir et al 2001;Skalski et al 2002;Weiland et al 2009). In addition, impoundments and passage facilities may delay the outmigration of juvenile salmonids, increasing their exposure to disease and predation.…”
Section: Introductionmentioning
confidence: 99%